Identification of the Vibrations Corresponding with Heart Sounds using Vibrational Cardiography - D'Mello, Yannick; Skoric, James; Hakim, Siddiqui; Aboulezz, Ezz; Clairmonte, Nathan; Lortie, Michel; Plant, David V. (2020 42nd Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2020)
Cardiography enables diagnostic and preventive care in hospitals and outpatient scenarios. However, most heart monitors do not distinguish the phases of the cardiac cycle. The transition between phases is indicated by the primary heart sounds. Objective: Automatically identify the vibrations corresponding to both heart sounds. Methods: Cardiac activity was monitored for 15 subjects while at rest, during exertion, and while performing static breath holds. The subjects consisted of 6 males and 9 females between the ages of 18-39 years with no known cardiorespiratory ailments. Motion corresponding to the heart sounds was identified using vibrational cardiography (VCG). The waveforms were processed to obtain quantities associated with their linear jerk and rotational kinetic energy. Results: The ability to identity the first vibration was evaluated using the heart rate as a figure of merit. Its correlation with electrocardiography (ECG) measurements produced a r 2 coefficient of 0.9887. The second vibration was compared with impedance cardiography (ICG) based on its delay from the ECG R-peak, and the fraction of the beat duration occupied by left ventricular ejection time. The comparisons produced r 2 values of 0.251 and 0.2797, respectively. Conclusion: The vibrations corresponding to both primary heart sounds have the potential to be analyzed using VCG. Significance: This study provides evidence of the feasibility of using VCG in identifying mechanical cardiovascular function. It facilitates non-invasive cardiac health monitoring in daily life.